Examining The Role of Religious Values in Mediating the Effect of Competitiveness and Brand Equity on SME Performance - Abdillah, Adil; Joenarni, Elly; Rachmawati, Eny; Rizkawati, Nidya (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to examine the influence of business competitiveness and brand equity on small business performance, with religious values as a mediating variable. In the context of small enterprises, competitiveness and brand strength are critical factors that determine business sustainability and growth. However, in religiously-influenced communities, religious values often shape how business owners make decisions, interact with customers, and manage their enterprises ethically. Design/methodology/approach: This research employs a quantitative approach using survey data collected from small business owners in a specified region. Path analysis is used to assess both direct and indirect relationships among the variables. Findings: The findings reveal that both business competitiveness and brand equity significantly affect business performance. Furthermore, religious values are found to mediate these relationships, enhancing the positive impact of competitiveness and brand equity on performance. These results highlight the importance of integrating spiritual dimensions into the strategic development of small businesses. Originality/value: This paper is original Paper type: a Research Paper